2023
DOI: 10.1002/cbdv.202201124
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Botanical Origin, Phenolic Compounds, Carotenoids, and Antioxidant Properties of Monofloral and Multifloral Bee Bread

Abstract: Bee bread is a unique natural product made by bees and good for human health. It has many bioactive molecules that can treat or prevent diseases. In this study, melissopalynological methods were used to examine five bee bread samples. Major plant sources found in bee bread were Lotus spp., Trifolium spp., and Xeranthemum spp., which are from the Fabaceae and Asteraceae families. Then, the amount of phenolic compounds and major carotenoids in bee bread (BB) samples were quantified. Gallic acid, caffeic acid, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The researchers identified 40 distinct phenolic compounds including the major phenolics quercetin and kaempferol in bee bread samples from different locations through the application of diverse analytical techniques, which are HPLC-DAD, HPLC-DAD-ESIMS, LC-MS, and UPLC-MSMS. [11] As in the literature, [33] quercetin emerges as the dominant polyphenolic compound in this study, exhibiting levels as high as 365.2 μg/g in the 2021 season and 11000.80 μg/g in 2022. Also, in both seasonal variations, ascorbic acid emerges as a prominent compound, [30] along with other bioactive flavonoids like isorhamnetin, kaempferol, [34] and hyperoside, as detailed in Table 2 (Figure 3).…”
Section: In Vitro Bioaccessibility Of Phenolicssupporting
confidence: 69%
“…The researchers identified 40 distinct phenolic compounds including the major phenolics quercetin and kaempferol in bee bread samples from different locations through the application of diverse analytical techniques, which are HPLC-DAD, HPLC-DAD-ESIMS, LC-MS, and UPLC-MSMS. [11] As in the literature, [33] quercetin emerges as the dominant polyphenolic compound in this study, exhibiting levels as high as 365.2 μg/g in the 2021 season and 11000.80 μg/g in 2022. Also, in both seasonal variations, ascorbic acid emerges as a prominent compound, [30] along with other bioactive flavonoids like isorhamnetin, kaempferol, [34] and hyperoside, as detailed in Table 2 (Figure 3).…”
Section: In Vitro Bioaccessibility Of Phenolicssupporting
confidence: 69%
“…Bee bread is reported to be rich in phenolic compounds and is, therefore, a functional food [ 27 , 28 ]. The results of the polyphenol analysis of bee bread samples collected from six different districts of Ardahan Province are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds have antioxidant, antimicrobial, and anti-inflammatory effects. It has also been reported that it is used in the treatment of diseases such as obesity, cancer, and diabetes. ,, It has been reported that poppy and bee bread are rich in phenolic components and bee bread is a functional food. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The TPC in bee bread-poppy sherbet was determined as 39.16 ± 0.57 at the beginning and 24.66 ± 0.38 on the 21st day. It was stated that the TPC of poppy sherbet was 31.388 ± 0.413 at the beginning and 27.152 ± 0.016 on the 20th day, while the TPC of bee bread was between 5.6 ± 0.1 and 11.4 ± 0.4 . It is stated that dried poppy flower contains 48.09 ± 0.31 mg GAE/g .…”
Section: Resultsmentioning
confidence: 99%